Color Harmony in Urban Environment - Al-Hinkawi, Wahda Shukur; Kamash, Nada Abdulmueen Hasan (Iraqi Journal of Architecture and Planning, 2018)
Many studies have addressed the problem of visual distortion a and disharmony in urban facades in terms of styles , formations , compositions and materials ... Etc., which reflected negatively on the urban form and aesthetic character of the city, and as a result of imposing of colors and clear dissonant in its design harmony. This research deals with the concept of harmony in architecture in general and urban design in particular, draw the most important formulas to achieve Color harmony in the urban facades, the research problem states that "there is no clear perception of the formulas to achieve color harmony in urban facade ", The research hypothesis in " color harmony may be achieved in urban facade through selected harmony formulas." Research hypothesis was tested in an urban housing project adopted, the color as a key element in the design of its facades, after some necessary adjustments to the application in the program (Adobe Photoshop CS5), research has concluded the following: 1 - the values of harmony achieved in different form according to the level of Color Harmony formula approved in the design, which indicates the integration between the relations of harmony and the formula of the Color Harmony. 2 – the change of the color harmony formula effects the value of formal harmony.